Radiation Use Efficiency in Different Row Orientation of Maize (Zea mays L.) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the Field Laboratory of Department of Environmental Science, Bangladesh Agricultural University, Mymensingh, Bangladesh to evaluate the radiation use efficiency (RUE) in different row orientation of maize, to determine parameters affecting RUE and to make a comparison of results of the study with previous results observed at different location of the world. The dry weight was taken at 7 days interval by destruction of five plants and kept them oven drier at 80oC for 48 hours and it was expressed as gm2. Dry matter accumulation values at different dates of sampling were regressed with the corresponding cumulative intercepted PAR values and the slope of the regression line was then taken as RUE. The efficiency of radiation utilization varies throughout the crop life cycle. Radiation use efficiency (RUE) was positively correlated to leaf area index (LAI), leaf chlorophyll content, extinction coefficient (k), incident radiation and total solar period of crops and negatively correlated to water stress and light reflection. RUE was highest in vegetative stage, where RUE was higher (0.89 gMJ-1 PAR) in N-S row orientation than E-W row orientation (0.75 gMJ-1 PAR), after that RUE decreased gradually in tasseling stage. Again RUE was slightly increased during maturity. RUE of maize was almost similar with the findings of other researchers and it ranged from 0.85 to 1.5 gMJ-1, it was due to similar plant architecture and stand duration.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22142 J. Environ. Sci. & Natural Resources, 7(1): 41-46 2014